Realization of the System Approach in Realiztion of Multicultural Education in General Educational Establishment - Kendzior, Petro (Pedagogical Discourse, 2013)
Multicultural education of students in a secondary school should be realized in various contexts, especially at the level of primary and middle school; it should be integrated into different types of educational activity. Systematic approach to multicultural education, in the framework of which students acquire the skills of socially acceptable behavior, civic responsibility and social partnership, should be realized at all levels of the educational process, and namely: educational courses; integration of multicultural content elements into existing subjects; availability of democratic school climate; properly organized out-of-school work; participation of school students in the activities of local ethnical communities and cultural societies, etc.